The Farmers' Bench—Connecting advanced technology to farmers' needs - International Livestock Research Institute (International Livestock Research Institute, 2017)
This 25-minute skit dramatises the contribution of the Biosciences eastern and central Africa-International Livestock Research Institute (BecA-ILRI) Hub to the continental agricultural research agenda. A lighthearted performance by research fellows, partners and staff, it sheds light on the BecA-ILRI Hub’s critical role in bridging high-end research with practical solutions for smallholder farmers.